(untitled) (Research, Society and Development, 2025)
The use of antidepressants has expanded significantly in Brazil in recent years, constituting a phenomenon of relevance for public health. Between 2020 and 2025, there was a notable increase in the prescription and consumption of these medications, driven both by the growth in diagnoses of depressive disorders and by the impact of social, economic, and health-related factors, such as the COVID-19 pandemic. This study is limited to analyzing trends in antidepressant use during the period in question, considering aspects related to users’ profiles, motivations for consumption, clinical and psychosocial repercussions, and regulation and control strategies. The general objective is to understand the implications of the increased use of antidepressants in Brazil, investigating the reasons behind the intensification of prescriptions, the effects observed on patients’ quality of life, and the possible consequences resulting from continuous use. The research was conducted through a literature review, using scientific articles and epidemiological databases from Google Scholar, LILACS, and SCIELO, focusing on articles in Portuguese. The results indicate that, although antidepressants play a fundamental role in the treatment of depression and other psychiatric disorders, indiscriminate use may be associated with psychological dependence, adverse effects, and excessive medicalization of social suffering. It is concluded that it is necessary to expand public mental health policies, strengthen therapeutic follow-up strategies, and promote awareness campaigns about the rational use of antidepressants, in order to balance clinical benefits and risk prevention.